PENGARUH FAKTOR MOTIVASI TERHADAP KEPUASAN KERJA DAN KINERJA PADA GURU SEKOLAH MENENGAH ATAS (SMA) DI SURABAYA (Proceeding SENDI_U, 2015)
This study aimed to analyze the influence of motivation factors on job satisfaction and performance at the highschool teacher in Surabaya. The sample data used in this study are primary data obtained from researchinstrument in the form of a questionnaire given to teachers of the high schools in Surabaya. From 350questionnaires distribute, total questionaire back and deserves to be treated at 240 questionnaires. Data analysisis a structural equation modelling program Lisrel 8.70. The selection of the samples tested in this study usingpurposive sampling method. The results of this research are : (1) didn’t significantly effect the workingenvironment on job satisfaction, (2) level of education have a significant effect on job satisfaction, (3) desires andpersonal expectations not significant effect on job satisfaction, (40 needs significant effect on job satisfaction, (5)working environment have a significant effect on performance, (6) levels of education not significant effect onperformance, (7) personal desires and expectations not significant effect on performance, (8) needs not significanteffect on performance, (9) job satisfaction have a significant effect on performance.Keywords: Working Environment, Levels of Education, Desires and Personal Expectations, Needs, JobSatisfaction, Performance